BIOLOGIYA SABAQLARÍNDA KÓRGIZBELI QURALLARDAN PAYDALANÍW - Turekeeva, A.J. (SCIENCE and SOCIETY, 2024)
The article contains information such as the importance of teaching in biology classes, the visual aids used, providing lessons with natural objects, auxiliary tools that accurately reproduce natural objects, the use of tables in teaching biology, and the content of technical educational tools.